The use of texts in the higher education online foreign language classroom: the case of Universidade Aberta - Martins, Margarida (2022)
"The use of texts in the higher education online foreign language classroom: the case of Universidade Aberta". CONFERENCE INFORMATION "Education, Technology & Culture in Crisis: Secondary & Higher Education in a Time of Virtual Instruction" Organizer: GIRES-Global Institute for Research Education & Scholarship Date: 15-16 May 2021 Place: Amsterdam (Virtual) More information: https://www.gires.org/activities/conferences/education-technology-culture-crisis-secondary-higher-education-virtual-instruction/